The Role of Fathers as Spiritual Models in Tahsin Al-Qur’an Learning Among Grade IX J Students at SMPN 2 Katapang - Dani Ramdani (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
The limited involvement of fathers in children’s religious education remains a significant concern, particularly in the development of Qur’anic recitation (tahsin) skills. This study aims to examine the role of fathers as spiritual models in supporting tahsin Al-Qur’an learning among Grade IX J students at SMPN 2 Katapang, Bandung Regency. The research was conducted from January to March 2026 using a qualitative approach with an intrinsic case study design. Data were collected through participatory observation, semi-structured in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña (2020). The findings indicate that the father’s role is reflected in three main patterns: exemplary behavior (modeling), active accompaniment (guidance), and consistent habituation in daily religious practices. The study concludes that fathers as spiritual role models play a significant role in enhancing the quality and consistency of students’ tahsin Al-Qur’an learning, both in school and at home.